Lithium ion secondary battery
Patent Information
- Application Number
- CN202610967420.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]随着锂离子电池向高能量密度方向发展,硅基材料凭借超高理论比容量成为提升电池容量的主流材料,但硅基材料在充放电过程中存在高达300%的剧烈体积膨胀,易造成极片表面固态电解质界面(例如SEI)膜的反复破裂与重构并诱发析锂副反应,产生大量气体和热量,加剧电池内部的热累积风险
(1)本发明通过在第二极片的第三活性层背离第二集流体的一侧表面设置第一表涂层,使其正投影覆盖第一极耳槽,不仅可以降低此处锂离子迁移的速率及局部电流密度,降低析锂风险,还能够在第二极片表面形成防护层,该防护层针对第一极耳位置的局部热量积聚区域以及热量扩散形成的热蔓延区域进行有效防护,能够减少由于第一极耳及其附近的高温区域的热量向第二极片传递后增加极片表面的固态电解质界面膜分解的风险,有效减少高温下电池内部的局部极片与电解液之间的副反应,减少产热,显著提升了电池的热安全性;
Smart Images

Figure CN122992142A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and specifically to a lithium-ion secondary battery. Background Technology
[0002] As lithium-ion batteries develop towards higher energy densities, silicon-based materials have become the mainstream material for increasing battery capacity due to their ultra-high theoretical specific capacity. However, silicon-based materials experience dramatic volume expansion of up to 300% during charge and discharge, which can easily cause repeated rupture and reconstruction of the solid electrolyte interface (SEI) film on the electrode surface, inducing lithium plating side reactions, generating a large amount of gas and heat, and exacerbating the risk of heat accumulation inside the battery. Meanwhile, under high-temperature abuse tests such as hot box tests, heat is often transferred to the cell interior through the tabs, causing heat concentration in the tab area. The SEI film on the electrode surface in and around the tab area is prone to decomposition, further aggravating side reactions between the active material and the electrolyte, increasing heat generation, and also causing thermal shrinkage of the separator. The combined effect of heat generation from silicon-based materials and localized heat accumulation in the tab area severely affects the thermal stability of the battery, easily leading to the risk of thermal runaway such as fire and explosion during high-temperature abuse tests.
[0003] Therefore, while achieving high capacity using silicon-based materials, how to effectively mitigate the internal heat accumulation caused by the high local temperature of silicon-based materials and electrode tabs, reduce the risk of thermal runaway under high temperature conditions, and improve the thermal safety performance of batteries has become a pressing technical problem to be solved in the current development of lithium-ion battery technology. Summary of the Invention
[0004] The purpose of this invention is to overcome the aforementioned problems in the prior art and provide a lithium-ion secondary battery. The lithium-ion secondary battery of this invention (hereinafter referred to as the battery) improves upon the electrode plates, thereby ensuring high capacity and high energy density while also exhibiting excellent high-temperature safety and cycle performance.
[0005] Based on this, the inventors of this invention propose the following solution: This invention provides a lithium-ion secondary battery, comprising a core wound from a first electrode, a second electrode, and a separator. The first electrode includes a first tab, and the second electrode includes a second tab. The lithium-ion secondary battery comprises a silicon-based material. The first electrode includes a first current collector, a first active layer on one side of the first current collector, and a second active layer on the other side of the first current collector. The first active layer has a first tab groove for accommodating the first tab, which exposes the first current collector, and a portion of the first tab is electrically connected to the first current collector within the tab groove. The second electrode includes a second current collector, a third active layer on one side of the second current collector, and a second active layer on the other side of the second current collector. A fourth active layer on the other side surface of the fluid; the second electrode also includes a first surface coating, which is disposed on at least a portion of the third active layer on the side surface facing away from the second current collector along the thickness direction of the second electrode, and a first insulating element is disposed on the surface of the first surface coating on the surface of the third active layer; in the thickness direction of the battery, the orthographic projection of the overlapping area of the first insulating element and the first surface coating on the surface of the third active layer covers the first tab groove; the first surface coating includes first particles, and the third active layer and the fourth active layer each independently include first active material particles, the average particle size of the first particles is D1, the average particle size of the first active material particles is D2, and D1 < D2.
[0006] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art: (1) By setting a first surface coating on the side of the third active layer of the second electrode that is away from the second current collector, the present invention can not only reduce the rate of lithium ion migration and local current density at this location and reduce the risk of lithium plating, but also form a protective layer on the surface of the second electrode. This protective layer effectively protects the local heat accumulation area and the heat spread area formed by heat diffusion at the location of the first electrode. It can reduce the risk of decomposition of the solid electrolyte interface film on the surface of the electrode after the heat from the first electrode and the high temperature area near it is transferred to the second electrode. It can effectively reduce the side reactions between the local electrode and the electrolyte inside the battery at high temperature, reduce heat generation, and significantly improve the thermal safety of the battery. (2) The present invention further limits the average particle size D1 of the first particle to be smaller than the average particle size D2 of the active material particles, so that the first particle can fill the micro gaps on the surface of the active layer, ensuring a smoother interface, eliminating air gaps, forming a dense and continuous protective layer, reducing local side reactions, and thus further synergistically improving the high-temperature safety performance and cycle performance of the battery; at the same time, the smooth interface of the first surface coating can further enhance the adhesion between the first insulating component and the first surface coating, reducing the risk of the first insulating component falling off at high temperature.
[0007] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description
[0008] Figure 1 The image shown is a front view I of the first electrode in an embodiment of the present invention.
[0009] Figure 2 The image shown is a front view II of the first electrode in an embodiment of the present invention.
[0010] Figure 3 The image shown is a top view of one side surface of the first electrode in an embodiment of the present invention.
[0011] Figure 4 The image shown is a front view of the second electrode in an embodiment of the present invention.
[0012] Figure 5 The diagram shown is a structural schematic of the core in an example of the present invention.
[0013] Figure label: 1. First electrode; 11. First current collector; 12. First active layer; 13. Second active layer; 14. First tab; 15. First tab groove; 16. Second tab groove; 17. Second surface coating; 18. Third insulating element; 19. Fourth insulating element; 2. Second electrode; 21. Second current collector; 22. Third active layer; 23. Fourth active layer; 24. Second tab; 25. Third tab groove; 26. Fourth tab groove; 27. First surface coating; 28. First insulating element; 29. Second insulating element; 3. Diaphragm. Detailed Implementation
[0014] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0015] This invention provides a lithium-ion secondary battery, comprising a core wound from a first electrode, a second electrode, and a separator. The first electrode includes a first tab, and the second electrode includes a second tab. The lithium-ion secondary battery comprises a silicon-based material. The first electrode includes a first current collector, a first active layer on one side of the first current collector, and a second active layer on the other side of the first current collector. The first active layer has a first tab groove for accommodating the first tab, which exposes the first current collector. A portion of the first tab is electrically connected to the first current collector within the tab groove. The second electrode includes a second current collector, a third active layer on one side of the second current collector, and a fourth active layer on the other side of the second current collector. The second electrode also includes a first surface coating. Along the thickness direction of the second electrode, the first surface coating is disposed on at least a portion of the third active layer on the side facing away from the second current collector. A first insulating element is disposed on the surface of the first surface coating on the surface of the third active layer. In the thickness direction of the battery, the orthographic projection of the overlapping area of the first insulating element and the first surface coating on the surface of the third active layer covers the first tab groove. It should be noted that the "first electrode groove" is formed by scraping off the first active layer in the corresponding area, so that the current collector in that area is exposed without the active layer covering it, and is used to accommodate the first electrode and achieve electrical connection with the first electrode.
[0016] In this invention, the first surface coating includes first particles, and the third active layer and the fourth active layer each independently include first active material particles. The average particle size of the first particles is D1, and the average particle size of the first active material particles is D2, where D1 < D2.
[0017] In one instance, D1 is 0.01μm-3μm (e.g., within the range of 0.01μm, 0.05μm, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm or any two of the above values).
[0018] In one instance, D2 is 5μm-25μm (e.g., within the range of any two of the following values: 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 23μm, 25μm).
[0019] To balance battery capacity and safety, this invention employs a silicon-based core structure with tabs placed within tab grooves on the electrode surface. Current can converge from both sides of the electrode to the tabs, shortening the current path, reducing internal resistance, and decreasing Joule heat generation during charging and discharging. However, due to the highly concentrated current density in the tab area, and its location within the core, heat dissipation is poor. When the battery is in a high-temperature environment, heat easily enters the core through the tabs, making this area a potential initiation point and source of thermal runaway. Furthermore, localized high-temperature zones and high-temperature heat diffusion zones form at locations with high contact resistance, such as the welding interface between the tabs and the tab grooves. In existing technologies, conventional protective tape is often pasted on the surface of the tabs to protect the welding area. However, under continuous high-temperature impact, the protective tape may fall off or break due to decreased adhesion. Once the tape fails, heat spreads violently along the area near the tab and the tab groove, causing the separator to shrink due to heat and triggering a short circuit between the positive and negative electrodes, inducing thermal runaway of the battery. As a result, it is difficult to effectively guarantee the safety pass rate of the battery in the hot box test.
[0020] Based on this, the inventors of this invention have conducted extensive targeted research, which effectively overcomes the above-mentioned problems, as detailed below: The area around the tabs experiences stronger heat concentration and faster heat conduction. During normal charge-discharge cycles, the current density near the tab grooves is concentrated, accelerating lithium-ion migration and causing the lithium-ion consumption rate in this area to far exceed the replenishment rate. This makes lithium plating more likely to occur in this area compared to other regions of the electrode that are farther away from the tabs. In particular, the second electrode area, corresponding to the location of the first tab along the thickness direction of the battery, suffers the most direct and severe thermal shock. The separator in this area is prone to thermal shrinkage, and the electrolyte on the electrode surface is easily oxidized, while the SEI film is easily decomposed. This further exacerbates the side reactions between the active materials in the electrode and the electrolyte, continuously increasing heat generation and thus triggering the risk of thermal runaway. Therefore, in order to enable the second electrode area to continuously resist the thermal shock of the first tab and its surrounding area, the present invention provides a first surface coating on the surface of the third active layer of the second electrode facing away from the second current collector, so that its orthographic projection covers the first tab groove. This not only reduces the rate of lithium ion migration and local current density in this area, reducing the risk of lithium plating, but also forms a protective layer on the surface of the second electrode. This protective layer effectively protects against the local heat accumulation and high-temperature heat spread area formed by heat diffusion at the first tab location. When the heat in the first tab area is too high, the heat will be transferred to the opposite separator and the surface of the second electrode through convection, conduction, radiation, etc. The first surface coating at this location is equivalent to forming a thermal barrier, which can prevent further heat diffusion and reduce the vicious cycle of heat generation and gas generation caused by the increase of local side reactions after heat diffusion. The first surface coating intercepts or disperses the heat accumulated at the first tab location, which helps to further prolong the heat penetration time and reduce the risk of battery fire and explosion caused by short circuit of the electrode after the separator corresponding to the first tab location shrinks. Meanwhile, a first insulating element is also provided on the surface of the first surface coating layer located on the surface of the third active layer, and the orthographic projection of the overlapping area of the first insulating element and the first surface coating layer covers the first electrode groove. This not only enhances the adhesion between the first insulating element and the first surface coating layer and reduces the risk of the first insulating element falling off at high temperature, but also further ensures that the second electrode area corresponding to the first electrode groove receives continuous thermal protection and physical isolation.
[0021] Further research in this invention revealed that the interface state between the first surface coating and the second electrode has a certain impact on battery performance. When the average particle size D1 of the first particles in the first surface coating is greater than or equal to the average particle size D2 of the first active material particles, it indicates that the first particles and the first active material particles are mismatched in size. This leads to a reduction in the effective contact area between the first surface coating and the active layer, an increase in interfacial contact resistance, and may trigger local electrochemical polarization. At the same time, the large-diameter first particles will also prolong the diffusion path of lithium ions, deteriorating the kinetic performance of the electrode. More importantly, during charge-discharge cycles and the repeated volume expansion and contraction of the active material, the large-diameter first particles are prone to cracking or peeling due to insufficient bonding force with the active layer and uneven stress distribution. This makes it difficult to form a continuous, uniform, and dense thermal protection layer on the surface of the active layer. This not only causes the inherent thermal insulation protection function of the first surface coating to fail, but also exacerbates the side reactions of electrolyte oxidation and internal heat accumulation, thereby seriously affecting the high-temperature safety and cycle stability of the battery. Therefore, by further limiting D1 < D2, the present invention allows the first particle to fill the microscopic gaps on the surface of the active layer, ensuring a smoother interface, eliminating air gaps, forming a dense and continuous protective layer, reducing local side reactions, and thus further synergistically improving the high-temperature safety performance and cycle performance of the battery; at the same time, the smooth interface of the first surface coating can further enhance the adhesion between the first insulating component and the first surface coating, reducing the risk of the first insulating component falling off at high temperatures.
[0022] In this invention, the average particle size D1 of the first particle and the average particle size D2 of the first active material particle can be obtained by conventional methods in the art, such as by scanning electron microscopy (SEM). Specifically, the battery is discharged to 0% SOC, the electrode sheet with the first surface coating and active layer is disassembled and removed. After soaking in dimethyl carbonate (DMC) solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt adhering to the electrode sheet. After drying, the positive electrode sheet is cut using an argon ion mill. The cross-section of the electrode sheet is then observed using SEM. The obtained cross-section is magnified to a certain factor (e.g., 5000x), and the maximum size between the edges of at least 50 first particles and 50 first active material particles is determined using image analysis software (such as ImageJ). The average values are then taken to obtain D1 and D2. If the number of first particles or active material particles is less than 50 at 5K magnification, the cross-section of the electrode sheet is moved until 50 particles can be measured.
[0023] In one example, the second active layer is provided with a second tab groove, which exposes the first current collector. The second tab groove and the first tab groove are disposed opposite each other along the thickness direction of the first electrode sheet. Along the thickness direction of the second electrode sheet, the first surface coating is also disposed on at least a portion of the surface of the fourth active layer facing away from the second current collector. A second insulating member is disposed on the surface of the first surface coating located on the surface of the fourth active layer. In the thickness direction of the battery, the orthographic projection of the overlapping area of the second insulating member and the first surface coating located on the surface of the fourth active layer covers the second tab groove.
[0024] When the second active layer has a second tab groove, heat can be transferred simultaneously from both sides of the location of the first tab to the corresponding second electrode area along the thickness direction of the battery. Therefore, by further providing a second insulating member and controlling the second insulating member to cover the second tab groove with the orthogonal projection of the overlapping area of the second insulating member and the first surface coating layer located on the surface of the fourth active layer along the thickness direction of the second electrode, the present invention can further reduce the risk of lithium plating and enhance thermal isolation, thereby improving the safety of the battery in hot box testing.
[0025] In this invention, the third active layer is provided with a third tab groove, which exposes the second current collector; the fourth active layer is provided with a fourth tab groove that accommodates the second tab, which exposes the second current collector; a portion of the second tab is electrically connected to the second current collector within the fourth tab groove; the third tab groove and the fourth tab groove are arranged opposite to each other along the thickness direction of the second electrode sheet.
[0026] In one example, the first electrode further includes a second surface coating layer disposed on at least a portion of the surface of the first active layer facing away from the first current collector and / or at least a portion of the surface of the second active layer facing away from the first current collector; a third insulating element is disposed on the surface of the second surface coating layer located on the surface of the first active layer, and a fourth insulating element is disposed on the surface of the second surface coating layer located on the surface of the second active layer; in the thickness direction of the battery, the orthographic projection of the overlapping area of the third insulating element and the second surface coating layer located on the surface of the first active layer covers the third tab groove, and the orthographic projection of the overlapping area of the fourth insulating element and the second surface coating layer located on the surface of the second active layer covers the fourth tab groove.
[0027] In this invention, the second surface coating includes second particles, and the first active layer and the second active layer each independently include second active material particles. The average particle size of the second particles is D3, and the average particle size of the second active material particles is D4, where D3 < D4.
[0028] In one instance, D3 is 0.01μm-3μm (e.g., within the range of 0.01μm, 0.05μm, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, or any two of the above values).
[0029] In one instance, D4 is 3μm-15μm (e.g., within the range of any two of the values 3μm, 5μm, 8μm, 10μm, 12μm, 15μm, or above).
[0030] The second tab and its surrounding area also generate high temperatures due to current concentration. This heat is transferred along the battery's thickness direction through the separator to the corresponding first electrode area, potentially causing lithium plating at the first electrode interface or exacerbating side reactions. To address this, by further depositing a second surface coating on the surfaces of the first and second active layers, and then depositing a third and fourth insulating element on the surface of the second surface coating, a heat-insulating buffer layer can be constructed on the corresponding first electrode area in the high-temperature zone of the second tab, blocking heat transfer from the second tab to the first electrode through the separator. The third and fourth insulating elements also enhance adhesion to the second surface coating, reducing the risk of them detaching at high temperatures, and further forming continuous thermal protection and physical isolation. This invention achieves stronger thermal protection by symmetrically and synergistically cooperating the thermal protection mechanisms on the second tab side and the first tab side within the core.
[0031] In this invention, the core has a flat area and arc areas located on both sides of the flat area; the first electrode includes a plurality of first flat segments located in the flat area and arranged sequentially from the inside to the outside along the core; the total area of the second surface coating on the first flat segments is S1, and the area of a single first flat segment is S2, wherein 2%≤S1 / S2≤400% (for example, within the range of any two values of 2%, 5%, 10%, 20%, 40%, 60%, 80%, 100%, 150%, 200%, 250%, 300%, 350%, 400%, or above).
[0032] In this invention, the second electrode includes a plurality of second straight segments located in the straight region and arranged sequentially from the inside to the outside along the core; the total area of the first surface coating on the second straight segments is S3, and the area of a single second straight segment is S4, wherein 2%≤S3 / S4≤400% (for example, within the range of any two values of 2%, 5%, 10%, 20%, 40%, 60%, 80%, 100%, 150%, 200%, 250%, 300%, 350%, 400%, or above).
[0033] It should be noted that the "straight region" refers to the portion of the core where the electrode extends in a straight line along its length without bending. Based on the above core structure, for the first or second electrode, each winding layer formed within the straight region during the winding process, and each segment extending in a straight line along the length of the electrode, is defined as a "straight segment," namely, the "first straight segment" and the "second straight segment." In the technical solution described in this invention, it can be considered that each "first straight segment" and "second straight segment" has the same dimension along the width direction of the core.
[0034] Because the heat concentration effect is stronger and the heat conduction rate is faster along the length of the electrode tab and its vicinity, heat will preferentially conduct along the left and right sides of the tab to the straight section of the winding layer where the tab is located. This causes a surge in heat in the straight section, resulting in large-area shrinkage of the corresponding separator area, which may lead to a short circuit due to direct contact between the electrodes. By limiting S1 / S2 or S3 / S4 to a suitable range, this invention can ensure that the first or second surface coating covers at least the high-temperature core area where heat accumulation is most concentrated, effectively mitigating the risk of severe separator shrinkage and battery short circuit in this area. On the other hand, it can also prevent the first or second surface coating from excessively occupying the surface of the active layer, which would absorb more electrolyte, reduce the sufficient wetting of the active layer by the electrolyte, slow down the lithium insertion / extraction reaction during battery charging and discharging, and affect the battery's rate, cycle and other performance characteristics. If S1 / S2 or S3 / S4 is less than 2%, the surface coating will not be able to fully cover the heat concentration area and high-temperature area formed by heat spread around the tab. Heat may still accumulate in large quantities in and around the tab, resulting in insufficient protection. If S1 / S2 or S3 / S4 is greater than 400%, the surface coating will excessively occupy the surface of the active layer of the electrode, which may increase the size in the thickness direction of the core, resulting in a decrease in battery energy density. It will also reduce the effective area on the electrode that participates in charging and discharging, reduce battery capacity, and thus reduce the battery's cycle and rate performance.
[0035] In this invention, S1, S2, S3, and S4 can be obtained by conventional methods in the art, such as image analysis. Specifically, the battery is discharged to 0% SOC, the electrode with the first and second surface coatings is disassembled and removed, each straight segment is marked, and orthographic projection images are taken under an optical microscope or scanning electron microscope. The boundary contours of the first surface coating, the second surface coating, and the first and second straight segments are identified by image analysis software, and S1, S2, S3, and S4 can be calculated.
[0036] In this invention, the first electrode is a negative electrode, and the second electrode is a positive electrode. The first active layer is located on the surface of the first current collector away from the center of the core, and the second active layer is located on the surface of the first current collector close to the center of the core; the fourth active layer is located on the surface of the second current collector away from the center of the core, and the third active layer is located on the surface of the second current collector close to the center of the core.
[0037] In this invention, the negative electrode sheet includes a negative electrode active layer, the negative electrode active layer includes the silicon-based material, the negative electrode active layer includes a first active layer and a second active layer, and the mass content w1 of silicon element in the negative electrode active layer is 5%-70% (for example, within the range of any two values of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or more); let A1=(S1+S3) / S2, where 6≤A1 / w1≤160 (for example, within the range of any two values of 6, 10, 20, 30, 50, 80, 100, 120, 140, 160 or more).
[0038] In one instance, 30% ≤ A1 ≤ 800% (e.g., within the range of any two values of 30%, 50%, 80%, 100%, 150%, 200%, 250%, 300%, 350%, 400%, 450%, 500%, 550%, 600%, 650%, 700%, 750%, 800%, or above).
[0039] As the silicon content in the negative electrode active layer increases, the volume expansion of silicon-based materials becomes more dramatic during charge and discharge, resulting in a thicker SEI film. This leads to a significant increase in heat generation from SEI film decomposition during battery hot-box testing and cycling. To ensure the total area of the surface coating is commensurate with the silicon content, this invention correlates the total area ratio of the first and second surface coatings in the first straight section with the silicon content parameter, satisfying a specific formula. Higher silicon content results in a corresponding increase in the total surface coating area, thus blocking more heat generated by SEI film decomposition and side reactions, reducing the risk of fire and explosion during hot-box testing. When A1 / w1 is too small (e.g., less than 6), the total area of the coating layer is too small relative to the silicon content, and it cannot adequately block the large amount of heat generated by the decomposition of the SEI film in a high-silicon system. When A1 / w1 is too large (e.g., greater than 160), the total area of the coating layer is too large relative to the silicon content, which will reduce the wetting efficiency of the electrolyte on the electrode. Furthermore, the excessive occupation of the electrode active layer surface by the coating layer may increase the size in the thickness direction of the core, resulting in a decrease in battery energy density. It will also reduce the effective area on the electrode for charging and discharging, reduce battery capacity, and decrease the lithium intercalation rate and capability of the negative electrode, thereby reducing the battery's cycle and rate performance, and even triggering the risk of lithium plating.
[0040] In this invention, the mass content w1 of silicon in the negative electrode active layer can be obtained by conventional methods in the art. For example, after discharging the battery to 0% SOC, the negative electrode sheet is disassembled and soaked in dimethyl carbonate (DMC) solvent for 12 hours, then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet. After drying, the negative electrode sheet is subjected to high-temperature treatment at 400°C in an inert atmosphere for 2 hours (e.g., in a tube furnace under nitrogen or argon atmosphere). The negative electrode active layer can then be peeled off from the negative electrode current collector, and the negative electrode active layer is collected as a test sample. Using a thermogravimetric analyzer (e.g., a TGA550 thermogravimetric analyzer), the sample amount is 5mg-15mg. Under an air or oxygen atmosphere, the temperature is increased from room temperature (25°C) to 900°C at a rate of 10°C / min, and held at 900°C for 40 minutes. This allows the non-silicon components in the negative electrode active layer to volatilize while the silicon is fully oxidized to silicon dioxide. Weigh the residual material. The silicon content in the negative electrode active layer can be obtained by the following formula: Silicon content in the negative electrode active layer = 7 × mass of residual material / (15 × mass of test sample).
[0041] In one example, the first surface coating is also located on the surface of the third active layer and disposed around the third tab groove.
[0042] In one example, the first surface coating is also located on the surface of the fourth active layer and disposed around the fourth tab groove.
[0043] In one example, the second surface coating is also located on the surface of the first active layer and disposed around the first tab groove.
[0044] In one example, the second surface coating is also located on the surface of the second active layer and disposed around the second tab groove.
[0045] The positional relationship of the surface coating surrounding the tab groove is illustrated by the example of "the second surface coating being located on the surface of the first active layer and surrounding the first tab groove". For example, along the length direction of the first electrode sheet, the first tab groove has a first side and a second side, and the second surface coating has a third side and a fourth side; along the width direction of the first electrode sheet, the first electrode sheet includes a first end face and a second end face, the first tab groove has a fifth side and a sixth side, and the second surface coating has a seventh side; wherein, the first side and the third side are close to the first end of the first electrode sheet, the second side and the fourth side are close to the tail end of the first electrode sheet, the fifth side is close to the first end face of the first electrode sheet, and the sixth side and the seventh side are close to the second end face of the first electrode sheet; the second surface coating is arranged adjacent to the first side, the sixth side, and the second side of the first tab groove. The first end face is close to the extension direction of the first tab, and the second end face is away from the extension direction of the first tab.
[0046] It should be noted that the length direction of the electrode sheet is consistent with the winding direction of the core, that is, the length direction of the electrode sheet is equivalent to the winding direction of the core, and the width direction of the electrode sheet is along the extension direction of the electrode tab. "The beginning end of the electrode sheet" refers to the end that first enters the winding center and begins to participate in the winding process, i.e., the winding start end; "the end of the electrode sheet" refers to the end that is finally wound to the outside of the core and fixed in place during the winding process, i.e., the winding end end.
[0047] like Figure 1 The figure shows a front view I of the first electrode in an embodiment of the present invention. As can be seen from the figure, the first electrode 1 includes a first current collector 11, a first active layer 12 located on one side of the first current collector and a second active layer 13 located on the other side of the first current collector. The first active layer is provided with a first tab groove 15 to accommodate the first tab 14, and the second active layer is provided with a second tab groove 16. The first electrode also includes a second surface coating 17, which is located on the surface of the first active layer and surrounding the first tab groove and on the surface of the second active layer and surrounding the second tab groove.
[0048] like Figure 2The figure shows a front view II of the first electrode sheet in an embodiment of the present invention. As can be seen from the figure, the first electrode sheet 1 includes a first current collector 11, a first active layer 12 located on one side of the first current collector, and a second active layer 13 located on the other side of the first current collector. The first active layer is provided with a first tab groove 15 to accommodate a first tab 14, and the second active layer is provided with a second tab groove 16. The first electrode sheet also includes a second surface coating 17, which is respectively disposed on: the surface of the first active layer and surrounding the first tab groove, the surface of the second active layer and surrounding the second tab groove, the surface of the first active layer facing away from the first current collector, and the surface of the second active layer facing away from the first current collector. Among them, the surface of the second surface coating on the surface of the first active layer is provided with a third insulating member 18, and the surface of the second surface coating on the surface of the second active layer is provided with a fourth insulating member 19.
[0049] like Figure 3 The image shown is a top view of one side surface of the first electrode in an embodiment of the present invention, wherein, Figure 3 (a) is the overall view. Figure 3 (b) is a magnified view of a portion of the image. From Figure 3 As can be seen in (a), the first active layer 12 is provided with a first tab groove 15 to accommodate the first tab 14, and the second surface coating 17 is located on the surface of the first active layer; from Figure 3 As can be seen in (b), along the length direction of the first electrode, the first electrode lug has a first side E1 and a second side E2, and the second surface coating has a third side E3 and a fourth side E4; along the width direction of the first electrode, the first electrode includes a first end face B1 and a second end face B2, the first electrode lug has a fifth side E5 and a sixth side E6, and the second surface coating has a seventh side E7; the second surface coating is arranged adjacent to the first side E1, the sixth side E6 and the second side E2 of the first electrode lug.
[0050] like Figure 4 The figure shows a front view of the second electrode in an embodiment of the present invention. As can be seen from the figure, the second electrode 2 includes a second current collector 21, a third active layer 22 located on one side of the second current collector, and a fourth active layer 23 located on the other side of the second current collector. The third active layer is provided with a third tab groove 25; the fourth active layer is provided with a fourth tab groove 26 for accommodating a second tab 24. The second electrode also includes a first surface coating 27, which is respectively disposed on: the surface of the third active layer and surrounding the third tab groove, the surface of the fourth active layer and surrounding the fourth tab groove, the surface of the third active layer facing away from the second current collector, and the surface of the fourth active layer facing away from the second current collector. A first insulating element 28 is disposed on the surface of the first surface coating on the surface of the third active layer, and a second insulating element 29 is disposed on the surface of the first surface coating on the surface of the fourth active layer.
[0051] This invention provides a second surface coating layer surrounding the first tab groove and / or the second tab groove on the surfaces of the first active layer and / or the second active layer on both sides of the first electrode, and a first surface coating layer surrounding the third tab groove and / or the fourth tab groove on the surfaces of the third active layer and / or the fourth active layer on both sides of the second electrode. This symmetrically and comprehensively encapsulates the heat source area of the tab, effectively blocking bidirectional heat conduction. If a surface coating layer is only provided on one side, heat may still diffuse to adjacent electrodes or separators through the side without a surface coating layer, forming a "thermal bridge" and reducing the thermal protection effect. The surface coating layers provided on both sides form symmetrical thermal protection on both sides of the electrode thickness, effectively reducing the aforementioned "thermal bridge" effect and improving the thermal safety of the battery. When batteries undergo high-temperature abuse tests (such as hot box tests), even when the separator in the tab groove and its vicinity partially shrinks, the surface coating can still act as a backup barrier to prevent direct contact between the electrodes. This significantly suppresses side reactions and heat diffusion into the battery from the tab location and its vicinity, avoids the risk of short circuits caused by direct contact between the electrodes due to separator shrinkage, improves the battery's pass rate in hot box tests, and reduces the risk of lithium plating near the tabs.
[0052] In this invention, the core has a flat region and arcuate regions located on both sides of the flat region. The first electrode includes a plurality of first flat segments located in the flat region and arranged sequentially from the inside to the outside of the core, and a plurality of first arcuate segments and a plurality of second arcuate segments arranged sequentially from the inside to the outside of the core on both sides of the first flat segments; the second electrode includes a plurality of second flat segments located in the flat region and arranged sequentially from the inside to the outside of the core, and a plurality of third arcuate segments and a plurality of fourth arcuate segments arranged sequentially from the inside to the outside of the core on both sides of the second flat segments.
[0053] In one example, the winding layer containing the first tab has a first straight section and a first arcuate section and a second arcuate section located on both sides of the first straight section; along the winding direction of the core, the second surface coating covers the first straight section and extends to the first and second arcuate sections. In the winding direction of the core, the dimension of the second surface coating in the first arcuate section is d1, and the dimension of the second surface coating in the second arcuate section is d2, 0 ≤ |d1-d2| ≤ .
[0054] In one example, the winding layer containing the second tab has a second straight section and a third and a fourth arcuate section located on either side of the second straight section; along the winding direction of the core, the first surface coating layer covers the second straight section and extends to the third and fourth arcuate sections. In the winding direction of the core, the dimension of the first surface coating layer in the third arcuate section is d3, and the dimension of the first surface coating layer in the fourth arcuate section is d4, 0 ≤ |d3-d4| ≤ .
[0055] The arc-shaped region is a stress concentration area in the core and also a sensitive area with uneven lithium-ion concentration distribution, making it prone to lithium plating during charging and discharging. When heat generated in the tab area is conducted along the electrode to the arc-shaped regions on both sides, the heat in the arc-shaped regions is difficult to dissipate, further exacerbating the thermodynamic instability of the arc-shaped regions. The surface coating covers the straight section of the winding layer containing the tab and extends appropriately to the arc-shaped sections on both sides. On the one hand, it forms a thermal protection layer in the arc-shaped sections, reducing the large accumulation of heat and minimizing the decomposition of the solid electrolyte film layer on the local surface of the arc-shaped region and the deterioration of the thermal stability of the active material at high temperatures, thereby reducing the risk of thermal runaway. On the other hand, when the electrode is a positive electrode, the first surface coating can act as a physical barrier, regulating the ion flux in the arc-shaped section of the positive electrode and alleviating local current concentration, thus suppressing lithium plating. This invention ensures the symmetry of the coating distribution on both sides of the arc segments by limiting the difference between the dimensions d1 and d2 of the second coating layer in the first arc segment (i.e., |d1-d2|) and the difference between the dimensions d3 and d4 of the first coating layer in the third arc segment (i.e., |d3-d4|) to a reasonable range. If |d1-d2| or |d3-d4| is too large, it will lead to uneven heat flow and ion conduction on both sides, causing polarization, reduced charge-discharge consistency, and thus inducing problems such as lithium plating and accelerated capacity decay, affecting the battery's rate performance, cycle life, and other performance characteristics.
[0056] It should be noted that those skilled in the art can make adaptive and reasonable adjustments to the values of d1 and d2 or d3 and d4 according to the specific size of the core and the actual position of the tabs, as long as the difference limitation conditions of |d1-d2| or |d3-d4| are met. The present invention does not limit the specific values of d1 and d2 as well as d3 and d4.
[0057] In this invention, d1 and d2 can be obtained by conventional methods in the art, such as image analysis. Specifically, the battery is discharged to 0% SOC. A portion of the winding layer containing the first tab, including a first straight section and a first and second arcuate sections located on either side of the first straight section, is taken as the test sample. The sample is placed on the stage of an optical image measuring instrument or a scanning electron microscope measuring instrument. After imaging, image analysis software is used to identify the actual contour boundaries of the second surface coating corresponding to the first and second arcuate sections. d1 and d2 are measured using the device's built-in size measurement module. Multiple measurements are repeated at the same location, and the average value is taken as the final test result. The test methods for d3 and d4 are the same as those for d1 and d2, and will not be described further here.
[0058] In one example, the first straight segment has a first arc segment and a second arc segment on each side. The first straight segment where the first tab groove is located is the first straight segment I. Along the opposite direction of the winding of the core (i.e., from the winding tail end to the winding start end), the first electrode also includes the first arc segment I, the first straight segment II, the second arc segment I, and the first straight segment III, which are sequentially connected to the first straight segment I. The second surface coating layer located on the surface of the first active layer can also sequentially cover the first straight segment I, the first arc segment I, the first straight segment II, the second arc segment I, and the first straight segment III.
[0059] In one example, the first electrode is a negative electrode. The first straight segment has a first arc segment and a second arc segment on either side. The first straight segment containing the first electrode tab groove is the first straight segment I. Along the opposite direction of the winding of the core, the first electrode also includes the first arc segment I, the first straight segment II, the second arc segment I, and the first straight segment III, which are sequentially connected to the first straight segment I. The second surface coating layer located on the surface of the first active layer can also sequentially cover the first straight segment I, the first arc segment I, the first straight segment II, the second arc segment I, and the first straight segment III.
[0060] In this invention, the second straight section has the third arc section and the fourth arc section on both sides, respectively; the second straight section where the first insulating member is located is the second straight section I. Along the opposite direction of the winding of the core, the second electrode also includes the third arc section I, the second straight section II, the fourth arc section I, and the second straight section III, which are sequentially connected to the second straight section I; the first surface coating layer located on the surface of the third active layer can also sequentially cover the second straight section I, the third arc section I, the second straight section II, the fourth arc section I, and the second straight section III.
[0061] In one example, the second electrode is a positive electrode. The second straight section has the third arc segment and the fourth arc segment on either side, respectively; the second straight section where the first insulating member is located is the second straight section I. Along the opposite direction of the winding of the core, the second electrode also includes the third arc segment I, the second straight section II, the fourth arc segment I, and the second straight section III, which are sequentially connected to the second straight section I; the first surface coating layer located on the surface of the third active layer can also sequentially cover the second straight section I, the third arc segment I, the second straight section II, the fourth arc segment I, and the second straight section III.
[0062] like Figure 5 The diagram shows a schematic of the core structure in an embodiment of the present invention. As can be seen from the diagram, the core has a flat region P and arc regions C located on both sides of the flat region. The negative electrode includes multiple first flat segments P1 located in the flat region and arranged sequentially from the inside to the outside of the core, and multiple first arc segments C1 and multiple second arc segments C2 arranged sequentially from the inside to the outside of the core on both sides of the first flat segments. The positive electrode includes multiple second flat segments P2 located in the flat region and arranged sequentially from the inside to the outside of the core, and multiple third arc segments C3 and fourth arc segments C4 arranged sequentially from the inside to the outside of the core on both sides of the second flat segments. The first flat segment where the first electrode lug 15 is located is denoted as the first flat segment I (P1-1). Along the opposite direction of the winding of the core, the first electrode also includes a first arc segment I (C1-1), a first flat segment II (P1-2), a second arc segment I (C2-1), and a first flat segment III (P1-3) that are sequentially connected to the first flat segment I. The second straight section where the first insulating element 28 is located is designated as the second straight section I (P2-1). Along the opposite direction of the winding of the core, the second pole piece also includes the third arc section I (C3-1), the second straight section II (P2-2), the fourth arc section I (C4-1), and the second straight section III (P2-3) which are connected to the second straight section I in sequence.
[0063] This invention forms a continuous surface coating in multiple straight and arc-shaped sections, which is equivalent to building a continuous and uninterrupted heat insulation barrier along the length of the electrode in the area of the electrode heat source and its vicinity. This can effectively prevent heat diffusion, suppress the occurrence of local side reactions, greatly reduce heat generation, and effectively avoid the risk of battery fire and explosion caused by electrode short circuit due to thermal shrinkage of the separator.
[0064] In this invention, the diaphragm includes a first surface and a second surface, and the diaphragm includes a third surface coating.
[0065] In one example, the diaphragm is disposed adjacent to the first tab groove, and the third surface coating is located on the second surface of the diaphragm, with the orthographic projection of the third surface coating covering the first tab groove in the thickness direction of the diaphragm.
[0066] In one example, the diaphragm is disposed adjacent to the fourth tab groove, the third surface coating is located on the second surface of the diaphragm, and the orthographic projection of the third surface coating covers the fourth tab groove in the thickness direction of the diaphragm.
[0067] In one example, the diaphragm is disposed adjacent to the second tab groove, and the third surface coating is located on the first surface of the diaphragm, with the orthographic projection of the third surface coating covering the second tab groove in the thickness direction of the diaphragm.
[0068] In one example, the diaphragm is disposed adjacent to the third electrode groove, the third surface coating is located on the first surface of the diaphragm, and the orthographic projection of the third surface coating covers the third electrode groove in the thickness direction of the diaphragm.
[0069] The tabs and their surrounding area are the main heat sources inside the battery core. When heat is conducted from the tabs to the surrounding area, the separator, as a directly adjacent component, is prone to thermal shrinkage at high temperatures, potentially leading to an internal short circuit. This invention addresses this by directly coating a third surface layer onto the separator surface, ensuring that the orthogonal projection of this surface layer along the separator's thickness direction covers the tab groove area. This allows heat from the tabs to be blocked and absorbed by the third surface layer before reaching the separator, effectively mitigating the direct heat flow impact from the tabs and thus inhibiting thermal shrinkage of the separator in the vicinity of the corresponding tab. This surface layer acts as a thermal buffer layer, effectively maintaining the structural stability of the separator at high temperatures. Simultaneously, this surface layer primarily provides localized thermal protection to the tab groove area, preserving the porosity and ion permeability of other areas of the separator, maintaining efficient ion transport channels for the electrolyte between the positive and negative electrodes. Therefore, it achieves excellent thermal protection while avoiding adverse effects on the battery's rate capability and cycle life.
[0070] In this invention, the surface of the negative electrode active layer is provided with a plurality of grooves, the depth of the grooves is h1, the width of the grooves is L1, the spacing between the grooves is L2, and the thickness of the second surface coating layer is h2, where h1 > h2.
[0071] In one example, h1 is 10μm-30μm (e.g., 10μm, 13μm, 15μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm, or any two of the above values). The groove depth refers to the vertical distance from the lowest point within the groove to the surface of the negative electrode. The groove depth can be obtained by measuring the depth of all grooves or at least 10 grooves on the surface of the negative electrode active layer using a 3D profilometer, and then taking the average value.
[0072] In one example, L1 is 50μm-200μm (e.g., within the range of any two values of 50μm, 70μm, 90μm, 110μm, 130μm, 150μm, 170μm, 190μm, 200μm, or above). The width of the groove refers to the shortest distance between two opposite edges of the orthogonal projection of a single groove on the negative electrode sheet. It can be obtained by testing the width of all grooves or at least 10 grooves on the surface of the negative electrode active layer using a 3D profilometer and then taking the average value.
[0073] In one example, L2 is 1mm-1.5mm (e.g., within the range of any two values of 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, or above). The groove spacing refers to the average distance between the two adjacent long sides of two adjacent grooves in the length or width direction of the negative electrode sheet. It can be obtained by testing the spacing of all grooves or at least 5 grooves on the surface of the negative electrode active layer using a 3D profilometer and taking the average value.
[0074] In one example, the second surface coating is at least partially disposed in the groove.
[0075] In this invention, the grooves can be prepared by laser etching, mechanical imprinting, or template method. For example, ultraviolet laser etching is used with a power of 5W-20W and a scanning speed of 200mm / s-800mm / s. The depth can be controlled by adjusting the laser power and the number of scans, and the required spacing can be obtained by controlling the processing path.
[0076] The surface of the negative electrode active layer has several grooves, which provide some space for the volume expansion of the silicon-based material, thus improving the cycle stability of the battery. Simultaneously, it shortens the contact distance between the electrolyte and the negative electrode active material, maintaining rapid ion transport capability and reducing the obstruction of lithium-ion migration by the surface coating, thereby improving the kinetics of the negative electrode side and ultimately enhancing the battery's rate performance. However, the grooves increase the contact area between the electrolyte and the negative electrode active material, but also increase the risk of side reactions that generate heat and gas. The second surface coating, at least partially filling the grooves, effectively suppresses side reactions, reduces heat and gas generation, and improves the battery's thermal performance. This invention controls the groove depth h1 to be greater than the second surface coating thickness h2, ensuring the grooves are not completely filled by the second surface coating, thus maintaining the electrolyte flow channel. If h1 ≤ h2, the grooves are completely covered by the surface coating, the ion transport channel is blocked, and the battery's rate performance decreases. Furthermore, the surface coating forms protrusions in the grooves, which can easily cause problems such as damage to the flatness of the electrode surface and poor adhesion of the insulating components. The gaps may become new areas for the accumulation of side reactions, leading to a decrease in the thermal stability of the battery.
[0077] In this invention, h2 can be obtained by conventional methods in the art, such as discharging the battery to 0% SOC, disassembling and removing the electrode, soaking it in dimethyl carbonate (DMC) solvent for 12 hours, rinsing it with DMC solvent to remove the lithium salt attached to the electrode, drying it, cutting the electrode with an argon ion milling machine using a CP laser, observing and determining the position of the second surface coating using a scanning electron microscope (SEM), randomly selecting 10 test sites on its surface, measuring the thickness of each site, and taking the average value.
[0078] In this invention, the thickness of the first surface coating is h3, and h2 ≤ h3.
[0079] In one instance, 0.5 ≤ h2 / h3 ≤ 1 (for example, within the range of any two values of 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or above).
[0080] In one instance, 0.6 ≤ h2 / h3 ≤ 0.9.
[0081] In the battery core, the negative electrode tab is located at the center, and the thermal conductivity of the negative electrode tab, negative current collector, and negative electrode active material is better than that of the positive electrode. Therefore, the heat load transferred from the negative electrode tab to the opposite positive electrode sheet is greater than the heat load transferred from the positive electrode tab to the negative electrode sheet. If the same thickness of surface coating is applied to both the positive and negative electrode sheets, insufficient protection may occur on the negative electrode tab side, while the excessively thick surface coating on the positive electrode tab side may lead to unnecessary resistance increases, affecting the rate performance of the battery. This invention sets the first surface coating on the positive electrode side, which bears a higher heat flux, to be thicker to effectively block a large amount of heat from the negative electrode tab, preventing oxygen release from the positive electrode material and thermal shrinkage of the separator; while the second surface coating on the negative electrode side is set to be relatively thin, which can minimize the obstruction of the surface coating to lithium ion intercalation in the negative electrode while meeting basic thermal protection for the positive electrode tab, thus reducing the risk of lithium plating.
[0082] In this invention, the first, second, and third surface coatings each independently include fillers and binders. The fillers include at least one of aluminum hydroxide, magnesium hydroxide, boron nitride, silicon dioxide, ammonium polyphosphate, polytetrafluoroethylene, and melamine cyanurate. When the surface coating formed by these fillers covers the active layer, it can reduce the direct contact between the active layer and the electrolyte near the tab area and reduce the risk of decomposition of the solid electrolyte film on the surface of the active layer, thereby improving the thermal safety of the battery. Furthermore, aluminum hydroxide and magnesium hydroxide undergo an endothermic decomposition reaction at high temperatures, releasing water of crystallization and absorbing a large amount of heat, thereby reducing the local temperature; boron nitride has high thermal conductivity, which can quickly disperse the heat generated by local hot spots along the coating plane, preventing a large accumulation of heat locally; ammonium polyphosphate can form an expanded carbon layer at high temperatures, isolating oxygen and heat transfer; silicon dioxide has good heat resistance and chemical stability, which can block and reduce side reactions between the active material and the electrolyte; polytetrafluoroethylene and melamine cyanurate can form a stable carbonized layer at high temperatures, playing a role in blocking heat and mass transfer. The adhesive includes at least one of the following: polyvinylidene fluoride (PVDF), PVDF-hexafluoropropylene copolymer, polyimide precursor (PI), polyamide-imide (PAI), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), SBR-CMC composite system, polyacrylic acid adhesive (PAA), polyacrylonitrile-based latex (PAN-based latex), polyacrylates, and cross-linked modified acrylate adhesives. The choice of adhesive is crucial to the long-term stability of the surface coating. PVDF has higher crystallinity and lower swelling degree than copolymerized PVDF, maintaining structural stability in the electrolyte; PI and PAI have higher heat resistance and mechanical strength; the SBR-CMC composite system is a commonly used adhesive system with good compatibility with the negative electrode active layer; PAN-based latex and cross-linked modified acrylate adhesives provide better flexibility and electrolyte resistance. Crosslinked modified acrylates include polymers formed by copolymerization of at least one monomer selected from acrylic acid, acrylates, methyl methacrylate, ethyl methacrylate, isooctyl acrylate, n-propyl acrylate, butyl acrylate, cyclohexyl acrylate, and 2-hydroxyethyl acrylate.
[0083] The batteries can all be assembled in accordance with conventional methods in the field.
[0084] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.
[0085] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0086] In the following examples, unless otherwise specified, all materials used are commercially available analytical grade.
[0087] The following examples illustrate the lithium-ion secondary battery of the present invention.
[0088] Example 1 (1) Preparation of positive electrode Step 1: Lithium cobalt oxide (D2 is 8.5μm), conductive agent (conductive carbon black and carbon nanotubes are mixed at a mass ratio of 1:1), and polyvinylidene fluoride (PVDF) are mixed at a mass ratio of 98.2:1:0.8. N-methylpyrrolidone is added and the mixture is stirred under vacuum until the mixture becomes a uniform and fluid positive electrode active layer slurry. Step 2: Mix silica (D1 is 0.02μm) and polyacrylic acid (PAA) at a mass ratio of 90:5:5, add deionized water as a solvent, and stir evenly to obtain the first surface coating slurry; Step 3: Uniformly coat the above-mentioned positive electrode active layer slurry onto both sides of the aluminum foil, and then apply the above-mentioned first surface coating slurry according to... Figure 4 The coating is uniformly applied to the surface of the positive electrode active layer, and after baking, rolling, and slitting, a positive electrode sheet is obtained. The active layer at a certain location on the positive electrode sheet is scraped off to form a third and fourth tab groove with fixed dimensions. The aluminum tab is then laser- or ultrasonically welded to the fourth tab groove to obtain the positive electrode tab; wherein, S3 / S4 is 200%; and the thickness h3 of the first surface coating is 5.5 μm. (2) Preparation of negative electrode Step 1: Mix the negative electrode material (artificial graphite and silicon carbon in a mass ratio of 79.5:20.5, with D4 of 6.3μm), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose in a mass ratio of 96.1:0.5:2:1.4, add deionized water, and stir under vacuum to prepare a negative electrode active layer slurry. Step 2: Mix silica (D3 is 0.02μm) and PAA at a mass ratio of 90:5:5, add deionized water as a solvent, and stir evenly to obtain the second surface coating slurry; Step 3: The above-mentioned negative electrode active layer slurry is uniformly coated on both sides of the copper foil, and the above-mentioned second surface coating slurry is uniformly coated on the surface of the negative electrode active layer. The foil is then dried in an oven at 80°C for 10 hours. After rolling, slitting, and sheet preparation, several grooves are etched on the surface of the negative electrode active layer using laser processing technology to obtain the negative electrode sheet. The active layer at a certain location of the negative electrode sheet is scraped off to form a first and second tab groove with fixed dimensions. Copper-plated nickel tabs are then welded into the first tab groove using laser or ultrasonic welding to obtain the negative electrode tab. The second surface coating is located on the side of the first active layer opposite to the first current collector and is orthogonally projected along the thickness direction of the battery, covering the third electrode groove and the second active layer on the side of the first active layer opposite to the first current collector and being orthogonally projected along the thickness direction of the battery, covering the fourth electrode groove; S1 / S2 is 200%; A1 is 400%; A1 / w1 is 80; the mass content of silicon element w1 in the negative electrode active layer is 5%; the depth h1 of the groove is 12.2μm; the width L1 of the groove is 121.4μm; the spacing L2 of the groove is 1.2mm; the thickness h2 of the second surface coating is 4.3μm; and h2 / h3 is 0.78. (3) Preparation of diaphragm A 6.5 μm thick polyethylene film is used as the substrate layer. A 2 μm thick boehmite-containing ceramic layer is coated on one side of the polyethylene film. Then, a 1 μm thick polyvinylidene fluoride (PVDF) adhesive layer is coated on the side of the boehmite ceramic layer facing away from the polyethylene film and towards the positive electrode, and on the other side of the polyethylene film. Silica (0.02 μm particle size) and PAA are mixed at a mass ratio of 90:5:5, and deionized water is added as a solvent. The mixture is stirred until homogeneous to obtain a third surface coating slurry. This third surface coating slurry is uniformly coated on the first and second surfaces of the separator. After baking, rolling, and slitting, the separator is prepared. The third surface coating is respectively located on: the first surface of the separator adjacent to the second electrode groove and its orthographic projection covers the second electrode groove; the first surface of the separator adjacent to the third electrode groove and its orthographic projection covers the third electrode groove; the second surface of the separator adjacent to the first electrode groove and its orthographic projection covers the first electrode groove; and the second surface of the separator adjacent to the fourth electrode groove and its orthographic projection covers the fourth electrode groove. (4) Battery preparation The positive electrode sheet prepared in step (1), the separator prepared in step (3), and the negative electrode sheet prepared in step (2) are stacked in sequence to ensure that the separator is between the positive and negative electrodes to play a role in isolation. Then, the bare battery is obtained by winding. The bare battery cell is placed in the outer packaging aluminum-plastic film, and the electrolyte (lithium hexafluorophosphate dissolved in a mixed solution composed of EC / DEC / EMC with a molar ratio of 1:1:1) is injected into the outer packaging. After vacuum sealing, standing, formation, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0089] Example 2 group This set of embodiments refers to Embodiment 1, except that the settings of A1, A1 / w1, and the first, second, or third coating layers are adjusted by changing S1 / S2 or S3 / S4, as follows: Example 2-1, S1 / S2 is 200%, S3 / S4 is 2%, A1 is 202%, A1 / w1 is 40.4; wherein, the first surface coating is only disposed on the side of the third active layer opposite to the second current collector and is orthogonally projected along the thickness direction of the battery to cover the first tab groove; In Example 2-2, S1 / S2 is 200%, S3 / S4 is 100%, A1 is 300%, and A1 / w1 is 60; wherein, the first surface coating is only disposed on the side of the third active layer opposite to the second current collector and is orthogonally projected along the thickness direction of the battery to cover the first tab groove. In Examples 2-3, S1 / S2 is 200%, S3 / S4 is 400%, A1 is 600%, and A1 / w1 is 120. In Examples 2-4, S1 / S2 is 2%, S3 / S4 is 200%, A1 is 202%, and A1 / w1 is 40.4; wherein, the second surface coating is only disposed on the side of the second active layer opposite to the first current collector and is orthogonally projected along the thickness direction of the battery to cover the fourth tab groove. In Examples 2-5, S1 / S2 is 100%, S3 / S4 is 200%, A1 is 300%, and A1 / w1 is 60; wherein, the second surface coating is only disposed on the side of the second active layer opposite to the first current collector and is orthogonally projected along the thickness direction of the battery to cover the fourth tab groove. Examples 2-6: S1 / S2 is 400%, S3 / S4 is 200%, A1 is 600%, and A1 / w1 is 120. In Examples 2-7, S1 / S2 is 28%, S3 / S4 is 2%, A1 is 30%, and A1 / w1 is 6; wherein, the first surface coating is only disposed on the side of the third active layer opposite to the second current collector and is orthogonally projected along the thickness direction of the battery to cover the first tab groove, and the second surface coating is only disposed on the side of the second active layer opposite to the first current collector and is orthogonally projected along the thickness direction of the battery to cover the fourth tab groove; Examples 2-8: S1 / S2 is 400%, S3 / S4 is 400%, A1 is 800%, and A1 / w1 is 160. In Examples 2-9, the surface of the diaphragm is not coated with a third coating.
[0090] Example 3 Group This set of embodiments is based on Embodiment 1, except that the depth h1 of the groove and the thickness h2 of the second surface coating are changed, as follows: Example 3-1, h1 is 12μm, h2 is 12μm; Example 3-2, h1 is 10μm, h2 is 12μm.
[0091] Example 4 group This set of embodiments is based on Embodiment 1, except that h2 / h3 is adjusted by changing the thickness h3 of the first surface coating, as detailed below: Example 4-1: h3 is 7.17 μm, h2 / h3 is 0.6; and the filler in the first, second, and third surface coatings is replaced with aluminum hydroxide of the same mass content, and the binder is replaced with polyvinylidene fluoride of the same mass content, wherein D1 is 2 μm and D3 is 2 μm; In Example 4-2, h3 is 4.78 μm and h2 / h3 is 0.9; the filler in the first, second, and third surface coatings is replaced with the same mass content of melamine cyanurate, and the binder is replaced with the same mass content of polyacrylonitrile-based latex, wherein D1 is 0.5 μm and D3 is 0.5 μm; In Examples 4-3, h3 is 8.6 μm and h2 / h3 is 0.5; In Examples 4-4, h3 is 4.3 μm and h2 / h3 is 1; In Examples 4-5, h3 was 3.58 μm and h2 / h3 was 1.2.
[0092] Comparative Example 1 This comparative example is based on Example 1, except that the battery does not have a surface coating.
[0093] Comparative Example 2 This comparative experiment was conducted with reference to Example 1, except that the average particle size D1 of the first particle and the average particle size D2 of the first active substance particle were changed, as follows: Comparative Example 2-1, D1 is 8.5 μm, D2 is 8.5 μm; Comparative Example 2-2, D1 is 10.3 μm and D2 is 8.5 μm.
[0094] Test case (1) Hot box test The batteries prepared in the examples and comparative examples were subjected to hot box tests at 130°C and 131°C, respectively. The specific test methods are as follows: At 25℃, the resulting batteries were discharged at a constant current of 0.2C to the lower limit voltage and left to stand for 5 minutes; then charged at a constant current of 0.5C to the upper limit voltage and kept constant until the current dropped to 0.02C; the fully charged batteries were placed in a hot chamber and heated to 130℃ and 131℃ at a heating rate of 5℃ / min, and held at the corresponding constant temperature for 60 minutes before the test ended. The judgment criterion was that the battery did not catch fire or explode within 60 minutes, which was considered a pass. For each example or comparative example, 10 samples were tested at each temperature, and the pass rate was recorded. The pass rate = number of passing batteries / total number of tested batteries, denoted as n / 10. The results are recorded in Table 1.
[0095] (2) Loop testing The batteries prepared in the examples and comparative examples were subjected to cycle tests, and the specific test methods are as follows: At 45°C, the batteries prepared in the embodiments and comparative examples of this invention were discharged at 1C to 3.0V, then allowed to stand for 10 minutes, and then charged at 1C to 4.55V with a cutoff current of 0.025C, followed by a 10-minute stand. The thickness of the battery at this point was recorded as the initial thickness h1. The batteries were then discharged at a rate of 1.2C to the cutoff voltage of 3.0V, allowed to stand for 10 minutes, and the discharge capacity was recorded as the initial capacity. This charging and discharging process was repeated until the 600th cycle of constant voltage charging was completed, followed by a 10-minute stand. The batteries were then discharged at 1.2C to 3.0V, allowed to stand for 10 minutes, and the discharge capacity was recorded as the capacity after cycling. The cycle capacity retention rate is calculated as: Cycle Capacity × 100% / Initial Capacity. The results are recorded in Table 1.
[0096] (3) Lithium plating test The batteries prepared in the examples and comparative examples were subjected to lithium plating tests. The specific test methods are as follows: The prepared battery was left to stand at 25±2℃ for 5 minutes, then discharged at 0.2C to the lower limit voltage of 2.8V, left to stand for 5 minutes, and then charged according to the charge-discharge cycle mechanism: charged at 3.5C to 4.55V, cut off at 0.025C, left to stand for 5 minutes, which constitutes one charge-discharge cycle. Then it was discharged at 0.7C to the lower limit voltage of 3V, left to stand for 5 minutes. After 20 cycles, the battery was disassembled, and the lithium plating state on the surface of the negative electrode was observed. The criteria for judging the lithium plating phenomenon on the negative electrode were as follows: "0" indicates no lithium plating; "1" indicates the lithium plating area as a percentage of the total negative electrode area is less than 10%; "2" indicates the lithium plating area as a percentage of the total negative electrode area is 10%-20%; "3" indicates the lithium plating area as a percentage of the total negative electrode area is greater than 20% and less than or equal to 30%; and "4" indicates the lithium plating area as a percentage of the total negative electrode area is greater than 30%. Record the results in Table 1.
[0097] Table 1 As shown in Table 1, the battery prepared in this invention exhibits a higher cycle capacity retention rate after 600 cycles at 45°C compared to the comparative example. Furthermore, it effectively suppresses heat diffusion in and around the tabs, improving the battery's thermal conductivity and safety. Simultaneously, it reduces the rate of lithium-ion migration and local current density near the tabs, lowering the risk of lithium plating at the negative electrode. The battery of this invention achieves a balance between high capacity, high energy density, and excellent high-temperature safety and cycling performance.
[0098] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A lithium-ion secondary battery, characterized in that, The lithium-ion secondary battery includes a core wound with a first electrode, a second electrode, and a separator, wherein the first electrode includes a first tab and the second electrode includes a second tab; the lithium-ion secondary battery includes silicon-based material. The first electrode includes a first current collector, a first active layer located on one side of the first current collector, and a second active layer located on the other side of the first current collector; the first active layer is provided with a first tab groove to accommodate the first tab, the first tab groove exposes the first current collector, and a portion of the first tab is electrically connected to the first current collector within the first tab groove. The second electrode includes a second current collector, a third active layer located on one side surface of the second current collector, and a fourth active layer located on the other side surface of the second current collector; The second electrode further includes a first surface coating. Along the thickness direction of the second electrode, the first surface coating is disposed on at least a portion of the surface of the third active layer facing away from the second current collector. A first insulating element is disposed on the surface of the first surface coating located on the surface of the third active layer. In the thickness direction of the battery, the orthographic projection of the overlapping area of the first insulating member and the first surface coating layer located on the surface of the third active layer covers the first tab groove. The first surface coating includes first particles, and the third active layer and the fourth active layer each independently include first active material particles. The average particle size of the first particles is D1, and the average particle size of the first active material particles is D2, where D1 < D2.
2. The lithium-ion secondary battery according to claim 1, wherein, The second active layer is provided with a second tab groove, which exposes the first current collector. The second tab groove and the first tab groove are arranged opposite to each other along the thickness direction of the first electrode sheet. Along the thickness direction of the second electrode, the first surface coating is also disposed on at least a portion of the fourth active layer on the side surface opposite to the second current collector, and a second insulating member is disposed on the surface of the first surface coating located on the surface of the fourth active layer; in the thickness direction of the battery, the orthographic projection of the overlapping area of the second insulating member and the first surface coating located on the surface of the fourth active layer covers the second tab groove.
3. The lithium-ion secondary battery according to claim 1 or 2, wherein, The third active layer is provided with a third tab groove, which exposes the second current collector. The fourth active layer is provided with a fourth tab groove that accommodates the second tab, which exposes the second current collector. A portion of the second tab is electrically connected to the second current collector within the fourth tab groove. The third tab groove and the fourth tab groove are arranged opposite to each other along the thickness direction of the second electrode sheet. The first electrode further includes a second surface coating, which is disposed on at least a portion of the surface of the first active layer facing away from the first current collector and / or at least a portion of the surface of the second active layer facing away from the first current collector; A third insulating element is provided on the surface of the second surface coating layer located on the surface of the first active layer, and a fourth insulating element is provided on the surface of the second surface coating layer located on the surface of the second active layer. In the thickness direction of the battery, the orthographic projection of the overlapping area of the third insulating member and the second surface coating layer located on the surface of the first active layer covers the third tab groove, and the orthographic projection of the overlapping area of the fourth insulating member and the second surface coating layer located on the surface of the second active layer covers the fourth tab groove. The second surface coating includes second particles, and the first active layer and the second active layer each independently include second active material particles. The average particle size of the second particles is D3, and the average particle size of the second active material particles is D4, where D3 < D4.
4. The lithium-ion secondary battery according to claim 3, wherein, The core has a flat area and arc areas on both sides of the flat area; the first electrode includes a plurality of first flat segments located in the flat area and arranged sequentially from the inside to the outside along the core; the total area of the second surface coating on the first flat segments is S1, and the area of a single first flat segment is S2, wherein 2%≤S1 / S2≤400%.
5. The lithium-ion secondary battery according to claim 4, wherein, The second electrode includes a plurality of second straight segments located in the straight region and arranged sequentially from the inside to the outside along the core; the total area of the first surface coating on the second straight segments is S3, and the area of a single second straight segment is S4, wherein 2%≤S3 / S4≤400%.
6. The lithium-ion secondary battery according to claim 5, wherein, The first electrode is a negative electrode, the second electrode is a positive electrode, the first active layer is located on the surface of the first current collector away from the center of the core, the second active layer is located on the surface of the first current collector close to the center of the core; the fourth active layer is located on the surface of the second current collector away from the center of the core, and the third active layer is located on the surface of the second current collector close to the center of the core. The negative electrode sheet includes a negative electrode active layer, the negative electrode active layer includes the silicon-based material, the negative electrode active layer includes a first active layer and a second active layer, and the mass content w1 of silicon element in the negative electrode active layer is 5%-70%; let A1=(S1+S3) / S2, where 6≤A1 / w1≤160; Preferably, 30% ≤ A1 ≤ 800%.
7. The lithium-ion secondary battery according to claim 1 or 2, wherein, The first surface coating is also located on the surface of the third active layer and is disposed around the third electrode groove; And / or, the first surface coating is also located on the surface of the fourth active layer and disposed around the fourth electrode groove; And / or, the second surface coating is also located on the surface of the first active layer and disposed around the first tab groove; And / or, the second surface coating is also located on the surface of the second active layer and disposed around the second tab groove.
8. The lithium-ion secondary battery according to claim 3, wherein, The diaphragm includes a first surface and a second surface, and the diaphragm includes a third surface coating. The diaphragm is disposed adjacent to the first tab groove, and the third surface coating is located on the second surface of the diaphragm. In the thickness direction of the diaphragm, the orthographic projection of the third surface coating covers the first tab groove. And / or, the diaphragm is disposed adjacent to the fourth electrode groove, the third surface coating is located on the second surface of the diaphragm, and the orthographic projection of the third surface coating covers the fourth electrode groove in the thickness direction of the diaphragm; And / or, the diaphragm is disposed adjacent to the second tab groove, the third surface coating is located on the first surface of the diaphragm, and the orthographic projection of the third surface coating covers the second tab groove in the thickness direction of the diaphragm; And / or, the diaphragm is disposed adjacent to the third electrode ear groove, the third surface coating is located on the first surface of the diaphragm, and the orthographic projection of the third surface coating covers the third electrode ear groove in the thickness direction of the diaphragm.
9. The lithium-ion secondary battery according to claim 6, wherein, The surface of the negative electrode active layer is provided with a plurality of grooves, the depth of the grooves is h1, and the thickness of the second surface coating layer is h2, where h1 > h2; Preferably, the second surface coating is at least partially disposed in the groove; Preferably, h1 is 10μm-30μm; Preferably, the width of the groove is L1, where L1 is 50μm-200μm; Preferably, the spacing between the grooves is L2, where L2 is 1mm-1.5mm.
10. The lithium-ion secondary battery according to claim 3, wherein, The thickness of the first surface coating is h3, and h2 ≤ h3; Preferably, 0.5 ≤ h2 / h3 ≤ 1; More preferably, 0.6 ≤ h2 / h3 ≤ 0.9.